2003
DOI: 10.2298/jsc0303235d
|View full text |Cite
|
Sign up to set email alerts
|

A stilbene from the heartwood of Maclura pomifera: Note

Abstract: Dried heartwood powder of Maclura pomifera, Moraceae, was extracted with acetone. Silica gel column chromatography (CC) of the crude extract yielded 2',3',4',5'-tetrahydroxystilbene (oxyresveratrol).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…The infrared spectrum of compound 1 also matched that of oxyresveratrol (data not shown). The 1 H-NMR and 13 C-NMR spectral patterns of compound 1 were in good agreement with those of standard oxyresveratrol and with those reported in the literature (data not shown) (Djapic et al 2003;Soekamtoa et al 2005). The results suggest that compound 1 is oxyresveratrol.…”
Section: Oxyresvertrol Was Identified From Mb Extractsupporting
confidence: 86%
“…The infrared spectrum of compound 1 also matched that of oxyresveratrol (data not shown). The 1 H-NMR and 13 C-NMR spectral patterns of compound 1 were in good agreement with those of standard oxyresveratrol and with those reported in the literature (data not shown) (Djapic et al 2003;Soekamtoa et al 2005). The results suggest that compound 1 is oxyresveratrol.…”
Section: Oxyresvertrol Was Identified From Mb Extractsupporting
confidence: 86%
“…Solvents A and B were 0.05% TFA/H 2 O and 0.05% TFA/CAN, respectively. The identity of oxyresveratrol with a purity of 97% from M. alba was confirmed by comparing its spectroscopic data with previously published data [45,46]. …”
Section: Methodssupporting
confidence: 57%
“…Peak 1 was isolated from the M. alba extract and identified as oxyresveratrol as shown in Figure 3. The NMR data (Additional file 1: Table S1), UV spectra data (Additional file 1: Figure S1A) and MS data (Additional file 1: Figure S1B) of oxyresveratrol in the study were analyzed and confirmed with those described elsewhere [45,46]. …”
Section: Resultsmentioning
confidence: 59%
“…By comparing their physical and spectroscopic data with those reported in the literature or analyzing their 2D-NMR spectral data, the known compounds ( Figure 1) were identified as moracin M (2) [12], moracin P (3) [13], resveratrol (4) [14], oxyresveratrol (5) [15], oxyresvera- [17], mongolicon F (8) [18], guangsangon J (9) [19], b-daucosterol (10) [20], and b-sitosterol (11) [20].…”
Section: Resultsmentioning
confidence: 99%